Палеогеографічна інтерпретація деяких археологічних матеріалів басейну Дніпра - Пазинич, В.Г. (Інститут археології НАН України, 2008)
Paper deals with comparison of geomorphology of two archeological sites. In the lower part of Vorskla River the artifacts lies on buried soil that contain remains of bog oak. Artifact age is about 5000 years. The age of bog oak, according to C14 analysis, constitutes 4920 years. At the same time, this level is defined as Würmian terrace on the geomorphology maps. Similar situation exists on some other sites, for example on Paleolithic site of Mira, situated on the left bank of Dnipro River, next to Konevske village.